The effect of a therapeutic exercise program in correcting some spine deviations and improving some functional indicators among middle school students (11-14) years old - شرشار عبد القادر; طاهر طاهر; جلول كمال بن الحاج (Journal of Sport Science Technology and Physical Activities, 2022)
This study aimed to prepare a rehabilitation program to treat some spinal deviations and reveal its effect on some functional indicators for middle school students, 11-14 years old. 12 students with spinal deviation (lumbosacral and lumbar concavity), and the experimental method was used for its suitability to the nature of this study. Finally, the researchers presented suggestions that might contribute to sending additional ideas about the necessity of implementing the proposed treatment program in schools to reduce the rate of spread of these deviations